Government of Meghalaya Annual Plan 1998-99 Draft Proposals Volume - I - Planning Commission (Planning Commission, 1998)
Area and location : Meghalaya, first carved an autonomous State with the two Hill districts of the United Khasi & Jaintia Hills, and the Garo Hills of Assam in 1970, became a full fledged State in January, 1972. It is one of the smallest States in India and is strategically located in the North East. It has an area of 22,429 sq. kms approximately. It is a strip of land spread along the northern boundary of Bangladesh and is bounded by that country on the South and partly from the West. the length of the international boundary is about 423 kms. the State is surrounded on the other side by Assam. Access to the State is mainly by road from Assam. the land surface of the Slate mostly comprises steep hills and deep gorges, with valleys and plains land being very limited.
Planning Department Government of Meghalaya